PENGARUH KEPEMIMPINAN, MOTIVASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI - Rahma Muti’ah; Mulkan Ritonga; Ayu Anora (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to investigate the influence of leadership, motivation, and job satisfaction on organizational commitment. Effective leadership, high motivation, and good job satisfaction are considered key factors in shaping an employee's commitment to the organization. This study uses a quantitative approach with a survey of office employees and PKS of PT. Serba Huta Jaya as many as 63 people as a population as well as a research sample. The data was collected using a questionnaire that measured the level of leadership, motivation, job satisfaction, and organizational commitment. Data analysis was carried out using descriptive statistical methods and multiple regression analysis to determine the relationship between these variables. The results of the study showed that there was a positive and significant relationship between leadership, motivation, and job satisfaction and organizational commitment both partially and simultaneously. This shows that effective leaders, a motivating work environment, and high levels of job satisfaction can increase employee commitment to the organization. These findings have practical implications for human resource management in developing strategies to increase organizational commitment. Managers and leaders need to pay attention to the importance of building effective leadership, creating a motivating work environment, and paying attention to employee job satisfaction as an effort to increase organizational commitment. Thus, this study contributes to the understanding of the factors that influence organizational commitment and provides a basis for the development of relevant management interventions in the workplace